The impact of physical activity on cumulative cardiovascular disease risk factors among Malaysian adults - Rasiah, R.; Thangiah, G.; Yusoff, K.; Manikam, R.; Chandrasekaran, S.K.; Mustafa, R.; Abu Bakar, N. (2015)
Background: Numerous studies have shown the importance of physical activity in reducing the morbidity and mortality rates caused by cardiovascular disease (CVD). However, most of these studies emphasise little on the cumulative effect of CVD risk factors. Hence, this study investigates the association between physical exercise and cumulative CVD risk factors among adults in three different age groups. Methods: Using a sample of 7276 respondents drawn from community centers, the REDISCOVER team gathered information on physical activity, CVD risk factors (obesity, diabetes, hypertension, hypercholesterolemia, tobacco use) and socioeconomic and demographic variables in Malaysia. Because the study required medical examination, a convenience sampling frame was preferred in which all volunteers were included in the study. Fasting blood samples and anthropometric (height, weight and more) measurements were collected by trained staffs. Socio-demographic and physical activity variables were recorded through questionnaires. A Chi-square test was performed to identify the bivariate association between the covariates (socioeconomic variables, demographic variables and physical activity) and outcome variable. The association between the main exposure, physical activity, and the outcome variable, cumulative CVD risk factors, was assessed using an ordinal logistic regression model, controlling for socioeconomic status and demographic influences in three different age groups, 35-49, 50-64 and 65 and above. Results: The mean age of participants is 51.8 (SD = 9.4). Respondents in the age groups of 35-49 (aOR(moderate) = 0.12; 95 % CI: 0.02 - 0.53) and 65 and above (aOR(high) = 0.58; 95 % CI: 0.24, 0.78) showed a statistically significant inverse relationship between physical activity and cumulative CVD risk factors. However, this relationship was not significant among respondents in the 50-64 age group suggesting the possible influence of other variables, such as stress and environment. Conclusions: The statistically significant results show a negative association between physical exercise and cumulative CVD risk factors. However, the lack of a significant relationship in the 50-64 age group suggests the need to include other considerations in future studies, such as stress and environment.